2021
DOI: 10.1002/admi.202100580
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric Hydrogels—A Promising Platform in Enhancing Water Security for a Sustainable Future

Abstract: anthropogenic activities that have led to saline intrusion and contamination of the existing freshwater sources, making the current approaches for water treatment even more difficult and costly. [2][3][4] This, in combination with the continuously rising global water demand, results in a rather pessimistic prediction that an additional 2000 billion m 3 of freshwater supply will be required by 2030 to meet the global demand, assuming no gains on the current state of water-production capacity and efficiency. [5,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(32 citation statements)
references
References 389 publications
(837 reference statements)
0
32
0
Order By: Relevance
“…129,130 Hydrogel, a 3D network capable of absorbing large amounts of water, has confirmed its potential as a multifunctional material platform to escort global water security, owing to the unique physicochemical characteristics, such as swellability, porosity, and hydrophilicity. 131 For example, hydrogel with large specific surface area could rapidly adsorb various pollutants and then realize recycle via the regeneration of active sites. 132 Superabsorbent hydrogel with bactericidal property could directly absorb microorganism-contaminated water and then extrude to produce the disinfected water.…”
Section: Particles and Hydrogelsmentioning
confidence: 99%
“…129,130 Hydrogel, a 3D network capable of absorbing large amounts of water, has confirmed its potential as a multifunctional material platform to escort global water security, owing to the unique physicochemical characteristics, such as swellability, porosity, and hydrophilicity. 131 For example, hydrogel with large specific surface area could rapidly adsorb various pollutants and then realize recycle via the regeneration of active sites. 132 Superabsorbent hydrogel with bactericidal property could directly absorb microorganism-contaminated water and then extrude to produce the disinfected water.…”
Section: Particles and Hydrogelsmentioning
confidence: 99%
“…It has been observed that the transition process from CI to CII is accompanied by modifications of the intensities corresponding to different crystallographic planes. The diffraction peaks characteristic of CI are presented in Figure 4a and appear at Bragg angles (2θ) of 14.6°, 16.2°, and 22.5°, which are typical for the crystallographic planes, (110), (1)(2)(3)(4)(5)(6)(7)(8)(9)(10), and (200), respectively. In the case of the CII, three characteristic cellulose lattice planes were identified in the XRD diffraction pattern (Figure 4b), and these appear at 12.1° assigned to the (110) plane, at 20.1° for the (1-10) plane, and at 21.8° for (200) plane, respectively.…”
Section: Crystallinity In Cellulose Allomorphs and Cellulose-based Hy...mentioning
confidence: 99%
“…Using the natural polymers in the preparation of the hydrogels represents an attractive option over the most of the synthetic counterparts, due to the wide design possibilities of some specific compositions and properties, providing, besides the support function, key features such as biodegradability, biocompatibility, and low latent toxicity [ 8 , 9 ]. Moreover, hydrogels based on natural polymers can be employed either for the sustained and controlled (stimuli-responsive systems) delivery of active pharmaceutical principles (mainly drugs and proteins) to different cultures and tissues, or as scaffolds for tissue engineering [ 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the fibrous mats and the foams, hydrogels are also gaining growing interest in the field of porous colorimetric indicators. Hydrogels are a category of three-dimensional polymer networks consisting of macromolecular chains linked through chemical bonds, and their most important characteristic is that they can absorb and retain large quantities of water or aqueous fluids [ 206 ] maintaining their structural integrity, as shown in Figure 7 a [ 207 ]. Hydrogel based materials have been developed for various applications including food packaging [ 208 ], biomedical [ 209 ] and water technologies [ 207 , 210 , 211 , 212 ], and as carriers of bioactive compounds.…”
Section: Structure-performance Dependencementioning
confidence: 99%
“…Hydrogels are a category of three-dimensional polymer networks consisting of macromolecular chains linked through chemical bonds, and their most important characteristic is that they can absorb and retain large quantities of water or aqueous fluids [ 206 ] maintaining their structural integrity, as shown in Figure 7 a [ 207 ]. Hydrogel based materials have been developed for various applications including food packaging [ 208 ], biomedical [ 209 ] and water technologies [ 207 , 210 , 211 , 212 ], and as carriers of bioactive compounds. The incorporation of anthocyanins [ 125 , 213 , 214 ] and other dyes [ 215 ] in hydrogels has been recently studied, thus the use of the hydrogel structure for the development of colorimetric indicators appears auspicious [ 69 ].…”
Section: Structure-performance Dependencementioning
confidence: 99%